Productive changes and their impact in the public health profiles of colombian Orinoquia - Rodríguez Triana, Diana
Social determinants of health explain the relationship among the environment, economic system and other factors that influence people health. The disease profiles are related with the environment, this condition permits to know the most common diseases in a region and to comprenhend the health condition in a specific population. This document reviews secondary information about disease profiles and their variations, between 2000 and 2014, in four states of Colombia: Arauca, Casanare, Meta and Vichada. At the same time, was conducted a research about productive transformations and their environmental effects in the four states. The information was analyzed and it permitted identify that preventable diseases are most common in those states.  Through the time was possible to identify rate disease variations, for this reason, promoting knowledge appropiation among affected populations can conscientize them about the influence of environment conditions and colectivity. Finally, education and health promotion and prevention strategies can manage to increase consciousness about social, environmental and economic determinants of health to transform habits and life styles around colective action.